Related and unrelated diversification strategy on performance / Wan Mohd Nazri Wan Daud - Wan Daud, Wan Mohd Nazri (Institute of Graduate Studies, UiTM, 2014)
Diversification strategy has been debated in the fields of strategic management and finance. Inconclusive evidences pertaining to the effect of diversification strategy and debt on performance prevail in developed countries. Some studies suggest doing empirical research in developing countries to search for fresh evidence to validate those claims. This study examines the effect of diversification and debt usage on performance. Multiple proxies of performance are used namely market, economic, risk adjusted and accounting measurements in order to select the best proxy to explain the relationship among variables. The method deployed is panel data analysis on a sample of 76 Malaysian firms from various industries for the period of 1994 to 2007.